2000
DOI: 10.1021/ma992067g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self-assembled Hydrogels by Stereocomplex Formation in Aqueous Solution of Enantiomeric Lactic Acid Oligomers Grafted To Dextran

Abstract: This paper describes a novel hydrogel concept, which is based on self-assembling of enantiomeric lactic acid oligomers (stereocomplex formation) grafted to dextran. The hydrogels are prepared in an all-aqueous environment. For this purpose, l- and d-lactic acid oligomers were coupled to dextran, yielding dex−(l)lactate and dex−(d)lactate, respectively. Upon dissolving each product in water separately and mixing the solutions, we observed that a hydrogel is formed at room temperature as demonstrated by rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
125
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(136 citation statements)
references
References 41 publications
7
125
0
Order By: Relevance
“…In this paper, we aim to report the synthesis and characterization of graft copolymers based on poly 2-acylamido-2-methyl-1-propane sulphonic acid (PAMPS) and dextran by ceric ammonium nitrate (CAN) induced solution polymerization technique [18][19][20]. Four grades of graft copolymers (Dx-g-PAMPS1 to Dx-g-PAMPS4) were synthesized by varying the amount of AMPS in the reaction feed [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we aim to report the synthesis and characterization of graft copolymers based on poly 2-acylamido-2-methyl-1-propane sulphonic acid (PAMPS) and dextran by ceric ammonium nitrate (CAN) induced solution polymerization technique [18][19][20]. Four grades of graft copolymers (Dx-g-PAMPS1 to Dx-g-PAMPS4) were synthesized by varying the amount of AMPS in the reaction feed [21].…”
Section: Introductionmentioning
confidence: 99%
“…An attractive class of physically crosslinked gels is those where gel formation is not instantaneous, but occurs a certain time after mixing the hydrogel components (e.g. stereocomplex gels [7][8][9][10]) or after a certain trigger (e.g. temperature [3,[11][12][13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…This gives the possibility to design different PLA-conjugated materials in hydrogel preparation. For example, Hennink et al reported on physical hydrogels based on the stereocomplexation of PLA-dextran conjugates (de Jong et al, 2000). L-and D-lactic acid oligomers were coupled to dextran to yield dex-(L)lactate and dex-(D)lactate.…”
Section: Stereocomplexationmentioning
confidence: 99%